2011
DOI: 10.1186/1748-717x-6-60
|View full text |Cite
|
Sign up to set email alerts
|

Combined low initial DNA damage and high radiation-induced apoptosis confers clinical resistance to long-term toxicity in breast cancer patients treated with high-dose radiotherapy

Abstract: BackgroundEither higher levels of initial DNA damage or lower levels of radiation-induced apoptosis in peripheral blood lymphocytes have been associated to increased risk for develop late radiation-induced toxicity. It has been recently published that these two predictive tests are inversely related. The aim of the present study was to investigate the combined role of both tests in relation to clinical radiation-induced toxicity in a set of breast cancer patients treated with high dose hyperfractionated radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
2
20
1
1
Order By: Relevance
“…A subsequent smaller study (n=16) using fresh lymphocytes from breast RT patients and a fluorescence-labelled inhibitor of caspases (FLICA) to detect apoptosis also found no difference in mean apoptotic fractions (190). Although not all studies were able to show a significant association of lymphocyte apoptosis with normal-tissue reaction, three studies in which associations with late reactions were significant showed a consistent negative correlation between the frequency of apoptosis and the risk of late reaction (194, 212, 213) while increased early cell death correlated with early toxicity (194, 196, 212). A large multicentre prospective validation study of the RILA assay in breast and prostate patients is currently undertaken as part of the EU-funded REQUITE project (214) initiated by the RGC.…”
Section: Functional Assaysmentioning
confidence: 91%
See 1 more Smart Citation
“…A subsequent smaller study (n=16) using fresh lymphocytes from breast RT patients and a fluorescence-labelled inhibitor of caspases (FLICA) to detect apoptosis also found no difference in mean apoptotic fractions (190). Although not all studies were able to show a significant association of lymphocyte apoptosis with normal-tissue reaction, three studies in which associations with late reactions were significant showed a consistent negative correlation between the frequency of apoptosis and the risk of late reaction (194, 212, 213) while increased early cell death correlated with early toxicity (194, 196, 212). A large multicentre prospective validation study of the RILA assay in breast and prostate patients is currently undertaken as part of the EU-funded REQUITE project (214) initiated by the RGC.…”
Section: Functional Assaysmentioning
confidence: 91%
“…An early study found increased apoptosis in breast cancer patients relative to controls but no significant difference between patients with and without late reaction after RT (207). Enhanced apoptosis detected by Annexin V was found to be associated with resistance to late toxicity in 26 breast cancer RT patients (194). A recent study tested early death of lymphocytes by staining with trypan blue 4h after irradiation with 2 Gy and found a significant association with early toxicity grade (196).…”
Section: Functional Assaysmentioning
confidence: 99%
“…However, in addition to killing cancer cells, ionizing radiation causes damage to normal tissues and cells [1], which may cause serious adverse reactions, such as diarrhea, abdominal pain, nausea, vomiting and bleeding, among others [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…But the difference was not confirmed when γ-H2AX foci were counted by fluorescence microscopy. A series of studies [18-24] used histone γ-H2AX as a marker to predict the toxicity in normal tissue during radiotherapy of tumor patients, however, with contradictory outcomes. Thus, some of the quoted studies [19,21-23] revealed no correlation between either acute or late side effects of radiation therapy (RT) and expression of histone γ-H2AX.…”
Section: Introductionmentioning
confidence: 99%